A quest on the students learning preferences / Nurul Hayani Abd Rahman ... [et al.] - Abd Rahman, Nurul Hayani; Ismail, Shaira; Shafie, Nani Ilyana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Individual learning preferences is seen in how students’ way of exchanging information, whether visual (learning by seeing), auditory (learning by hearing), and kinesthetic (learning by doing). Dunn and Dunn's learning style defines how each learner begins to concentrate on, process, absorb, and remember new and complex ideas (Dunn, 2001). Some students sequentially process their experiences and knowledge, while others do it randomly; some students make decisions analytically, while others decide on the whim of their feelings. Meanwhile, some students are visually orientated, others geared to be vocally focused, and some students thrive in learning in groups, while others prefer to learn in isolation at home and other examples (Ismail et al., 2010). The wide range of ages, experiences, levels of preparedness, culture, gender, and other factors in the student population have produced various learning styles and preferences. Consequently, it compels academicians, academic boards, learning providers, or lecturers to satisfy students' needs and preferences and enhance their understanding level and successful learning process (Dantas & Cunha, 2020).